PERENCANAAN SUPERBLOK SEBAGAI MODEL PENGEMBANGAN PEMBANGUNAN PUSAT KOTA BEKASI - Atie Ernawati (Faktor Exacta, 2010)
Bekasi as one of hinterland cities has been growing very fastly. Traffic jam happens everywhere at the traffic hours, high polution and a very sunny day that has become an image for Bekasi, where used to recognize as ‘kota Perjuangan’ Green areas no longer exists and very hard to find in Bekasi. Horizontal development of Bekasi is not alowed any more. The increasing of population, quality of living society, and the quality of the centre Bekasi environment have become a vertically demand. Superblock model of development has been considered as one of development concept that suitable to employ in Bekasi. It is hoped that, the development of superblock can accommodate the need of settlement, retail, office, education, hotel, healthy, recreation, sport, etc, around Bekasi. Therefore, the high of mobility and growth in Jakarta can be decentralized in Bekasi. Superblock has become a part of cosmopolitan life style, which busy and civilized Superblock concept suitable or Bekasi where still growing and developing. Traffic jam and pollution can be decreased because many people will only take a walk to reach many strategic places. If they have to travel long distance, they can use public transportations which pass through superblock area. This research is done to feasibility of superblock concept implementation in central of developing Bekasi. This research used qualitative deskriptive analysis method, the result of this research can be proposal for Bekasi city government and stakeholders, for the development of Bekasi in the future. Keyword: Bekasi, planning, area, superblock, development.